Addressing cancer patient and caregiver role transitions during home hospice nursing care. Issue 5 (October 2019) - Hudson, Janella; Reblin, Maija; Clayton, Margaret F.; Ellington, Lee
Abstract: Objective: Many family caregivers and hospice patients experience role changes resulting from advancing illness and the need for increased caregiver responsibility. Successful navigation of conflicts that arise because of these role transitions has been linked to higher quality of patient care and improved caregiver bereavement adjustment. Nursing communication with patients and their caregivers plays an important role in facilitating these transitions. Our objective is to describe patient-caregiver-nurse communication during transitions at end of life. Method: A secondary, qualitative analysis was conducted on transcripts. Using an iterative process of constant comparison, coders inductively categorized nurse, caregiver, and patient communication behavior into overarching themes. Participants were home hospice nurses and cancer patient/spouse caregiver dyads; participants were >45 years of age, English speaking, and cognitively able to participate. Research took place in the home during nurse visits. Result: Nineteen unique home hospice visits were analyzed. Patient-caregiver conflict occurred in two major content themes (1) negotiating transitions in patient independence and (2) navigating caregiver/patient emotions (e.g., frustration, sadness). Nurse responses to transition conflict included problem-solving, mediating, or facilitating discussions about conflicts. Nurse responses to emotional conflict included validation and reassurance. Significance of results: Our findings provide insight into the topics and processes involved in patient and caregiver transitions in home hospice and the role hospice nursing communication plays in mediating potential conflict. Nurses are often asked to take on the role of mediator, often with little conflict resolution communication education; results can be used for nursing education.